The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1111/j.1751-1097.1977.tb07445.x
|View full text |Cite
|
Sign up to set email alerts
|

ON THE ORIGIN OF GLOW PEAKS IN EUGLENA CELLS, SPINACH CHLOROPLASTS AND SUBCHLOROPLAST FRAGMENTS ENRICHED IN SYSTEM I OR II

Abstract: Abstract— The origin of glow peaks (thermoluminescence) was investigated in isolated spinach chloroplasts and Euglena cells by pretreatment with various concentrations of 3‐(3,4 dichlorophenyl)‐1,1‐dimethylurea (DCMU)†, different light intensities, and after mild heating at various temperatures. Experiments are also reported on subchloroplast fractions enriched in pigment systems I (PSI) or II (PSII) (prepared under conditions to reduce destruction of membranes by excessive detergent contact). These results pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…This finding has been further corroborated by subsequent experimentation by several workers using bundle sheath chloroplasts of C-4 plants that apparently lack PSII and, therefore, show very weak TL. The inhibition of PSI activity by HgCl 2 does not affect the glow peak yield of isolated chloroplast (Sane et al, 1977;Horvath et al, 1978). Several other studies using herbicides and inhibitors that interact with PSI electron flow supports this conclusion.…”
Section: Historical Perspectivesupporting
confidence: 68%
See 1 more Smart Citation
“…This finding has been further corroborated by subsequent experimentation by several workers using bundle sheath chloroplasts of C-4 plants that apparently lack PSII and, therefore, show very weak TL. The inhibition of PSI activity by HgCl 2 does not affect the glow peak yield of isolated chloroplast (Sane et al, 1977;Horvath et al, 1978). Several other studies using herbicides and inhibitors that interact with PSI electron flow supports this conclusion.…”
Section: Historical Perspectivesupporting
confidence: 68%
“…Major TL bands are missing in etiolated leaves. Intermittent illumination to greening leaves which does not develop Mn clusture properly do not show the TL bands (Inoue et al, 1976;Sane et al, 1977). Misra et al (1998b) reported a gradual increase in the Q and B band from base to apex of that wheat leaves greening under continuous illumination, which confirms a developmental gradient across the wheat leaf lamina and a gradual development and organization of the photosynthetic PSII complexes.…”
Section: Stress Induced Changes In Tl Glow Peaksmentioning
confidence: 59%
“…Light emission can be obtained from preilluminated samples by slow heating [the glow curve technique (Arnold and Sherwood, 1957;Arnold and Azzi, 1968) with four or more bursts of emission at different temperatures (Shuvalov and Litvin, 1969;Arnold and Azzi, 1971;Desai et al, 1975;Sane et al, 1977)l. Rapid heating (temperature-jump) also causes preilluminated chloroplasts to emit a pulse of delayed light ; Jursinic and Govindjee, 1972;Malkin and Hardt, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of the B-band to Q-band occurs due to inhibition of electron transfer between Q A and Q B by DCMU, which enables the stabilization of Q A − as a negative charge detectable by TL instead of Q B − . Appearance of the Qband requires a functional water-splitting complex (40). Figure 2B shows the TL glow curves observed when 15 μM DCMU was added in control and RR-treated thylakoids.…”
Section: Resultsmentioning
confidence: 96%